Sensitivity to change of quadriceps and hamstrings muscle wearable electromyography outcomes during a professional soccer match - Kalema, R. N.; Duhig, S. J.; Finni, T.; Arumugam, A.; Pesola, A. J. (Journal of Sports Sciences, 2025)
Textile electromyography (EMG) was used to investigate neuromuscular activity during professional soccer matches, providing insights into performance optimization and injury prevention. This explorative study aimed to (1) describe the EMG activity of the quadriceps and hamstrings and (2) identify the metrics most sensitive to changes between the first and second half. Seven players (age: 23.1 ± 5.7 years; height: 1.82 ± 0.05 m; weight: 77.6 ± 10 kg) were evaluated. EMG outcomes included EMG amplitude, intensity distribution, and usual bout duration for dominant (D) and non-dominant (N.D) muscles. Hamstring activity averaged 47% (D) and 43% (N.D) of %EMGMVC, while quadriceps averaged 32% (D) and 27% (N.D). Most time was spent at the lowest EMG intensity and 13% at the highest intensity. Bout amplitudes (37-54%EMGMVC) and durations (14-17s) varied between muscle groups and limbs. The hamstrings` usual EMG bout amplitude (N.D) was the most sensitive, showing a 12% reduction (effect size [ES] = 0.64, p = 0,01). The most substantial percentage change was observed in the hamstrings` duration > 100% EMGMVC (D), which decreased by 27% (ES = 0.14, p = 0.57) with other metrics showing smaller reductions. This study highlights the potential of textile EMG to quantify neuromuscular demands during soccer matches, offering valuable tools for performance monitoring and tailored interventions to enhance training and prevent injuries.